Interrelations of Plague Microbe and Fleas from Geographically Separated Populations - L. P. Bazanova; G. A. Voronova; S. A. Kosilko (Проблемы особо опасных инфекций, 2010)
Studied were the peculiarities of interrelations of plague microbe from Hentei natural focus of Mongolia and fleas Citellophilus tesquorum of three geographic populations (Zabaikalskaya and Tuvinskaya from the natural plague foci and Olkhonskaya from plague-free territory. The functional contacts (etiological agent - vector) between the plague microbe and fleas from geographically separated populations from the focal territory were shown to be possible. Plague microbe that circulates in the territory of Hentei natural focus in Mongolia can form the proventriculus block in C. tesquorum from Trans-Baikal and Tuva. The infected insects can transfer the agent to animals that subsequently suffer from generalized infectious process. These data assume the possibility of C. tesquorum-mediated circulation of plague microbe from Mongolia in case of its import to the Trans-Baikal Region and to Tuva.